The relationship between nurses’ perceived organizational, supervisor and co-worker support, psychological well-being and job performance - Tiryaki Sen, Hanife; Yildirim, Aytolan (Journal of the Pakistan Medical Association, 2023)
Objective: To examine the relationship involving nurses’ perception of organisational, supervisor and co-worker support, psychological well-being and job performance. Methods: The cross-sectional, correlational study was conducted from June 2016 to January 2017 after approval from the ethics review committee of Istanbul Medipol University, Istanbul, Turkiye, and comprised nurses working in public or private sector and being in their current employment for at least one year. Data was obtained using Organizational Support, Co-Worker Support, Supervisor Support, Psychological Well-Being and Job Performance scales. Data was analyzed using SPSS 26. Results: Of the 1056 nurses, 896(84.8%) were women and 160(15.2%) were men. The overall mean age was 30.69±7.53 years (range: 17-59 years) and mean professional experience was 9.31±7.66 years (range: 1-36 years). Conclusion: Organisational, supervisor and co-worker support increased psychological wellbeing. Supervisor and co-worker support had a positive effect on job performance, but organisational support did not. Psychological wellbeing also increased job performance. Psychological well-being had a mediating role in the effect of organisational, supervisor and co-worker support on job performance. There was a positive relationship between perceived support, psychological wellbeing and job performance of nurses. Key Words: Co-worker support, Job performance, Organisational support, Psychological well-being, Supervisor support.